The Role of Incubation in Ancient Greek Asklepieions - Aneta Liwerska-Garstecka (Athens Journal of History)
The sanctuaries of Asklepios served a healing function in the Greek world throughout antiquity. In modern historiography, it is believed that the sick were treated there by incubation, i.e., sleeping in the temple to obtain a divinatory dream. However, the sources are not clear on this matter. In this article, I analyse four sources that, in my opinion, are the most representative of the issue of treatment methods in the Asklepieions. From the classical period, inscriptions describing healings from Epidauros and the comedy "Wealth" by Aristophanes are extremely important, while from Roman times they include "The Sacred Tales" by Aelius Aristides and the Apellas’ inscription from Epidauros. It is significant that none of these sources describes the incubation ritual, and the treatment methods presented in them are rational from the viewpoint of contemporary medicine. Incubation was practiced in the Asklepieions, but its role, in my opinion, was much smaller than commonly believed.